Assessing the impact of cloud-based services on the talent management of employees - Liu, Dan; Darbandi, Mehdi (Emerald Group Publishing Ltd, 2022)
Purpose Fundamental literature exists on the employment of diverse information technology (IT) innovations relied on utility computing, a little experimental literature exists on cloud computing adoption by medium enterprises. So, this essay aims to analyze the determinants of the acceptance of cloud computing in medium-sized organizations. It also targets the impact of cloud-depended services on employers' talent management in the analysis areas of research reports, hypotheses and frameworks used by them. Design/methodology/approach Cloud computing is a novel and notable development in the network application field with a novel IT viewpoint. The present investigation aims to assist and enrich the scientific argument regarding the phenomenon nominated cloud computing from a managerial perspective. A quantitative study design was utilized to gather and analyze the data. In total, 345 employees from different medium enterprises reported their perspectives via an online survey. Partial least squares was used to evaluate the model of the study. The investigation was performed from April 2020 to November 2020. Findings As expected, the empirical analysis results revealed that cloud computing adaption drivers positively and significantly associated with talent management. The results showed that organizational level is the most important factor in the effectiveness of talent management. Further, this study established a cloud strategy that moderates the relationships between cloud computing adaption drivers and talent management. As a general result, organization managers must implement cloud computing to improve organizational performance, reduce costs, enhance organizational innovation and reduce repetitive work. So, international trade facilitates and helps the country's economy. Research limitations/implications There are still some drawbacks of this analysis that require addressing the findings. Initially, the authors gathered a country's data. Second, by considering multiple significant structures from four aspects, they established the study model. Third, utilizing one-time cross-sectional data, the suggested model was evaluated. As a proposal, future researchers could investigate cloud computing adoption drivers' outcomes within other organizations. Originality/value This research presents a straightforward and easy model for understanding the cloud's effect on employee talent management. By systematizing the unrelated studies on the subject and organizing those contributions into strong managerial literature paradigms, such an aim has been accomplished.
Keywords: Information technology; Human resource; Employee; Cloud computing; Talent management; Medium enterprises